1986
DOI: 10.1111/j.1365-2605.1986.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor stimulates lactate production and inhibits aromatization in cultured Sertoli cells from immature rats

Abstract: The addition of epidermal growth factor (EGF) at nanomolar concentrations to cultures of Sertoli cells from 16-day-old rats induced more than a 2-fold stimulation of lactate production after 12 h of incubation. The effects of EGF, insulin and FSH on lactate production were very similar and the concentrations that produced half maximal stimulation were 11, 22 and 25 ng/ml or, in molar terms, 1.8, 3.5 and 0.6 nM for EGF, insulin and FSH, respectively. No synergistic or additive effects of these hormones on lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…After addition of serum to Sertoli cells this stimulatory effect of FSH on oestradiol production was inhibited [3]. In a previous paper we have shown that EGF may be one of the active principles in serum responsible for this inhibitory effect since EGF inhibits the FSH-stimulated aromatization in Sertoli cells from immature rats whereas insulin had no effect [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After addition of serum to Sertoli cells this stimulatory effect of FSH on oestradiol production was inhibited [3]. In a previous paper we have shown that EGF may be one of the active principles in serum responsible for this inhibitory effect since EGF inhibits the FSH-stimulated aromatization in Sertoli cells from immature rats whereas insulin had no effect [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sertoli cells were isolated as described by Oonk et al Ill], with slight modifications as reported earlier [4]. Briefly, decapsulated testes from 16-day-old Wistar rats were dispersed twice in phosphate-buffered saline (PBS), containing 0.5 mg/ml collagenase and 20/~g/ml deoxyribonuclease, both times for 30 min at 37°C in a shaking water bath at approx.…”
Section: Isolation and Culture Of Sertoli Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observations have been made on the regulation of lactate production by different locally produced factors. In this regard, EGF (Nehar et al 1993), IL1 (Nehar et al 1998) and TNF in porcine Sertoli cells (Nehar et al 1997) and insulin, insulin-like growth factor-I (Oonk et al 1989), EGF (Mallea et al 1986), PModS (Mullaney et al 1994), FSH and IL1 (Riera et al 2001) in rat Sertoli cells, act as regulators of lactate secretion. A distinct participation of these hormones on the stimulation of the different biochemical steps that will ultimately lead to increased lactate production has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…En effet, les cellules de la lign~e germinale ne m~taboli-sent pas le glucose mais utilisent pr~f~ren-tiellement le lactate provenant des cellules de Sertoli [54]. La FSH, rinsuline mais aussi des facteurs locaux comme IGF I, EGF augmentent la production de lactate par les cellules de Sertoli [36,45,54,59]. Ces molecules stimulent la production de lactate en favorisant, ~ court terme, la captation de glucose (principalement en augmentant les transporteurs de glucose).…”
Section: B) Action Indirecte Via Les Cellules De Sertoli 9 Par L'inteunclassified